Dialogue and Heroes: Bakhtin and existential perspectives on supervision (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
The purpose of the essay is to explore the possibility of using some insights of the Russian philosopher of the dialogic word and literary scholar Mikhail Bakhtin in supervision, from an existential perspective. The essay ends with a case. Translations from Swedish and French are mine, when otherwise not stated.
Keywords: Bakhtin; dialogue; existential supervision; existential psychotherapy